2014
DOI: 10.1007/s13277-014-2895-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in IL-4/IL-13 pathway genes and glioma risk: an updated meta-analysis

Abstract: Polymorphisms in interleukin (IL)-4/IL-13 pathway genes have previously been reported to be associated with glioma susceptibility, although results are inconsistent. We therefore performed an updated meta-analysis to determine a more precise estimation of this relationship. Twelve eligible studies were identified by searching PubMed, EMBASE, Web of Science, and the Cochrane Library electronic databases. Nine polymorphisms in genes within the IL-4/IL-13 pathway (IL-4 rs2243250, rs2070874, rs2243248, IL-4R rs180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Then, the new WHO classification published in 2021 included more molecular biomarkers [ 25 ]. Since then, a diverse set of biomarkers have been implicated as prognostic indicators in gliomas, including checkpoint molecules (PD-1, CTLA-4, TIM-3) [ 26 , 27 , 28 ], growth/angiogenesis proteins (EGFR) [ 29 ], and cytokines (TGF-β, IL-4, IL-13) [ 30 , 31 ]. Among them, the effects of IL-4/IL-4 receptors were investigated in the last decade [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the new WHO classification published in 2021 included more molecular biomarkers [ 25 ]. Since then, a diverse set of biomarkers have been implicated as prognostic indicators in gliomas, including checkpoint molecules (PD-1, CTLA-4, TIM-3) [ 26 , 27 , 28 ], growth/angiogenesis proteins (EGFR) [ 29 ], and cytokines (TGF-β, IL-4, IL-13) [ 30 , 31 ]. Among them, the effects of IL-4/IL-4 receptors were investigated in the last decade [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stratification by source of control did not substantially reduce the heterogeneity in the subgroups, suggesting that ethnicity and source of control did not fully explain the heterogeneity among studies. Two previous meta-analyses have analyzed the association between IL-13 gene rs20541 polymorphism and glioma susceptibility [6,19]. For the study by Chen et al [19], only the recessive model was assessed, and no association was found.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous meta-analyses have analyzed the association between IL-13 gene rs20541 polymorphism and glioma susceptibility [6,19]. For the study by Chen et al [19], only the recessive model was assessed, and no association was found. In this study, the rs1800925 polymorphism was also tested with the susceptibility to glioma, but still no association was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existing IL-4R was closely related to tumor genesis by numerous mechanisms [ 25 ]. For example, the polymorphisms in the interleukin (IL)-4/IL-13 pathway was reported previously to be associated with glioma [ 27 ]. Therefore, IL-4R-based tumor targeting drug delivery could be used for the treatment of several tumors.…”
Section: Introductionmentioning
confidence: 99%